(3cJGH GdbJd hGdbJGds - (3CHh eMeO GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdQSj, GdQSj,J (B246 (3g` s
(3ChdgG (B:s
(3SFd GdbGSe YeG jLH Hg GdbJd hGdbJGd , hjMd Hg YfO Gddg GdSHG hGdCehGd abGd jMd GdOe hGdeGd GdSHC hjhLH GdHQGAI hGdYOGhI hGdHZVGA s
(3BNQgG (B:s
(3bGd Gddg (B_ (3SHMGfg (B( (3GdPjf caQhG hUOhG Yf SHjd Gddg ROfGge YPGHkG ahb GdYPGH deG cGfhG jaSOhf (B) (3hgPG MOg GdPi HdZ ajg Edjg s
(3de jced eDdaI HbjI GdcJGH GfXQ fgGjI GdeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B171s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs